SISTEM PENGELOLA KEUANGAN DAN INFORMASIPADA MUSALA AL-MUJADID BERBASIS WEBSITE - Haryo Bismantoko (2021)
In the implementation of financial fund management activities and information activities on musala al-Mujadid still use manual methods. The management of financial funds and activity information in this manual way is very inefficient because it takes a lot of time in the process of calculating and delivering information. Financial and information management applications are created using HTML and PHP, MySQL as database servers, and are designed using prototyping methods. The result of this study is an application of financial and information managers who are expected to make the management of lecture activities, the list of prayer imams, prayer schedules, infak payments, payment of death funds, payment of zakat fitrah, payment of sacrifices and recording of money in and out.